The Practicing Hidden Curriculum in Improving the Quality of Islamic - Ely Sumanti, Putri Imamah Nurkhalis Ritonga; Ely Sumanti, Putri Imamah Nurkhalis Ritonga; Ely Sumanti, Putri Imamah (BiCED Proceeding, 2024)
The curriculum, which is a written plan, plays an important role in determining what students should learn. The curriculum not only includes academic knowledge, but also teaches social, emotional, and professional skills that are essential for the broader development of the individual. Various aspects of life are affected by the rapid growth of technology and science. This includes changing the role of schools as educational institutions. The essence of humanity remains the main foundation in guiding the learning process even though technology continues to develop and change. So, in this case it certainly cannot be separated from the implementation of the curriculum. This research discusses the hidden curriculum. Hidden curriculum is an important component of education that includes norms, values and attitudes that are instilled indirectly in daily life at school. It is not explicitly mentioned in the formal curriculum, but it is crucial for shaping students' social interactions, school performance and the development of non-academic skills, such as attitudes and social skills. This research method is a qualitative method of literature study, used to collect data by finding sources and reconstructing from various sources, including books, journals, and previous research.This research encompasses a recent discussion as it addresses the use of the hidden curriculum in this day and age, which is still too rigid in the knowledge of the general public. Therefore, this research can provide new insights.